Pengaruh Model Pembelajaran Oral Reading Fluency (ORF) Berbantuan Media Video Animasi terhadap Keterampilan Membaca Lancar Peserta Didik Kelas III SDN Kalumbuk - Amril, Riri Riani; Kharisma, Annisa; Rossa, Rona (Lembaga Yasin AlSys, 2025)
The low reading fluency skills among third-grade students in Indonesian language learning at SDN 20 Kalumbuk serve as the background of this study, given that strong reading ability is essential to support comprehension and overall academic success. This research aims to examine the effect of the Oral Reading Fluency (ORF) model assisted by animated video media on students’ reading fluency skills. A quasi-experimental design was employed using a non-equivalent posttest-only control group design. The population included all third-grade students, with Class IIIB as the experimental group using the ORF model assisted by animated videos, and Class IIIA as the control group receiving conventional instruction using similar media. The instrument used was a reading fluency skills test assessed through a rubric covering aspects of pausing, intonation, vocal expression, and reading comprehension. Data analysis was conducted using a t-test, which showed a significance value (2-tailed) of 0.021 < 0.05, indicating a significant difference between the two groups. The study concludes that the application of the ORF model assisted by animated video significantly improves students’ reading fluency. The findings imply that the ORF model can serve as a strategic alternative in Indonesian language instruction to enhance literacy skills at the elementary school level.